The Quality of Construction and Utilities Test Items for XI Grade Vocational High School Building Competencies Design and Information Design Skills - Hilmawan Wibawanto; A.G Tamrin; Aryanti Nurhidayati (Universitas Sebelas Maret, 2019)
This research aims to determine the quality of building construction and utility test on class XI SMK expertise competency of building modeling design and information. Quality of test based on qualitative and quantitative analysis. This research was quantitative descriptive. The subjects of the research are all students of class XI DPIB in SMKN 2 Surakarta and SMKN 5 Surakarta. The data were collected through documentation, observation, and questionnaires. The result indicates that the test item in SMKN 2 Surakarta and SMKN 5 Surakarta have good quality. Test item in SMKN 2 Surakarta qualitatively is following the test writing guidlines with score 95,7%, test item quantitatively has good quality on validity, reliability, discrimination index and distractor effectiveness but are bad in difficulty index, students’ perceptions explain that the test has a good quality with score 76%. Test item in SMKN 5 Surakarta qualitatively is by the test writing guidlines with score 91,7%, test item quantitatively has good quality on validity, reliability, discrimination index and difficulty index but are bad in distractor effectiveness, students’ perceptions explain that the test has a good quality with score 72,3%.